Tradeoff Between Aggregate Efficiency and Interregional Equity: A Static Analysis - Mera, Koichi (Quarterly Journal of Economics, 1967)
I. Introduction, 658. — II. General methodology, 659. — III. Transformation analysis with fixed coefficient production functions, 663. — IV. Numerical examples with Cobb-Douglas production functions, 666. — V. Conclusions, 673. — Appendix, 674.